Institutionalization of Democratic Governance Practices In Regional Development Planning: Implementation Of Musrenbang - Nurdin, Nani Harlinda; Mirsa, Sitti; Dahlan, Dahlan; Suaib, Muhammad Ridha (Universitas Negeri Makassar, 2024)
This study aims to analyze and describe the process of institutionalizing democratic values in development planning based on the regulatory system, normative system and cognitive cultural system in the Musrenbang implementation in Bone Regency. This research uses a descriptive qualitative approach through case studies. Data collection was carried out from September 2020 to March 2021 through observation, interviews, and documentation. Data analysis uses data reduction, data presentation, verification, and drawing conclusions. The results of the study found that (1) democratization in the Musrenbang in Bone Regency based on the regulatory system was not well institutionalized. This is due to the rule-making process which is still top-down and does not involve all stakeholders. Besides that, there is no monitoring of the enforcement of the rules and no sanctions have been set for the existing rules. (2) Democratization based on the normative system is also not well institutionalized, although the provisions regarding musrenbang are available but have not been fully complied with by stakeholders (3) Democratization based on the cognitive cultural system has been well institutionalized. This is shown that results in decisions in Musrembang by prioritizing mutual agreement/consensus, and the results of decisions taken in Musrembang are agreed upon between the stakeholders involved. Besides that, the people of Bone are strongly influenced by